Developing Online Czech Proofreader Tool: Achievements, Limitations and Pitfalls - Hlaváčková, Dana; Žižková, Hana; Dvořáková, Klára; Pravdová, Martkéta (Bohemistyka, 2022)
This paper deals with achievements, limitations and pitfalls of developing the Online Czech Proofreader Tool (OCPT). The Tool has been developed in cooperation with the Department of Czech language of the Faculty of Arts of Masaryk University, the Institute of Theoretical and Computational Linguistics of the Faculty of Arts of Charles University, the Czech Language Institute of the Czech Academy of Sciences and Seznam.cz since 2019. The article describes the linguistic data used and tools and modules that constitute the OCPT and indicates the limitations of using an online web-based proofreader tool, especially in areas where mere application of formal rules for language error detection is not sufficient. The article also brings up the drawbacks of developing the OCPT which include occurrence of false-positives.